This I Believe - Grady, Henry Francis (Tufts Archival Research Center, 2006)
Henry Grady describes some of his experiences as a diplomat, particularly during race riots in India between Hindus and Muslims, and explains why to live a good life with dignity one must follow the golden rule and "Love thy Neighbor as thyself." This episode is a rebroadcast of an earlier airing.